Blueprints Visual Scripting for Unreal Engine : build professional 3D games with Unreal Engine 4's Visual Scripting system - Sewell, Brenden (Community experience distilled., 2015)
Whether you are an experienced game designer or artist looking to test your latest idea, or a complete novice looking to build their first video game, this is a great place to start learning how to build complex game mechanics quickly and easily without writing any text code. No programming experience required!